Radio-protective role of antioxidant agents - Alireza Shirazi; Ehsan Mihandoost; Seied Rabie Mahdavi; Mehran Mohseni (Frontiers Media S.A., 2012)
Ionizing radiation interacts with biological systems to produce reactive oxygen species and reactive nitrogen species which attack various cellular components. Radio-protectors act as prophylactic agents to shield healthy cells and tissues from the harmful effects of radiation. Past research on synthetic radio-protectors has brought little success, primarily due to the various toxicity-related problems. Results of experimental research show that antioxidant nutrients, such as vitamin E and herbal products and melatonin, are protective against the damaging effects of radiation, with less toxicity and side effects. Therefore, we propose that in the future, antioxidant radio-protective agents may improve the therapeutic index in radiation oncology treatments.